PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP NILAI PELANGGAN DAN DAMPAKNYA PADA KEPUASAN PELANGGAN DISTRO MODESTO SAMPANGAN - M Faisal Safrianto, 11.05.51.0051; Soliha, Euis (Students Journal of Economic and Management, 2015)
This study examined two independent variables, namely the quality of products, and the perception that prices could affect the value and customer satisfaction. The purpose of this study was to analyze the influence of the two independent variables on the value and customer satisfaction distributions Modesto Sampangan Semarang This study was conducted by questionnaire to 100 customers Modesto Sampangan Semarang distributions obtained by using purposive sampling method, where researchers have criteria or specific objectives of the sample to be studied. The sample in this study is that consumers who have bought clothes in Modesto distributions Sampangan Semarang Testing in this study using validity (KMO) product moment and loading factors, reliability testing with Alpha Croanbrach, multiple linear regression analysis, t test to test and prove the research hypothesis. The results of this study stated that the quality of the product and price perception positive and significant impact on customer value and customer value and significant positive effect on customer satisfaction, whereas for product quality and price perception has no effect and no significant effect on customer satisfaction Keywords: Variable Quality Product, Price Perception, Customer Value, Customer Satisfaction